Identification of novel OCT4 genetic variant associated with the risk of chronic hepatitis B in a Korean population. (29th September 2016) - Shin, Joong‐Gon; Cheong, Hyun Sub; Lee, Kwanghyun; Ju, Bong‐Gun; Lee, Jeong‐Hoon; Yu, Su Jong; Yoon, Jung‐Hwan; Cheong, Jae Youn; Cho, Sung Won; Park, Neung Hwa; Namgoong, Suhg; Kim, Lyoung Hyo; et al.
Abstract: Background & Aims: Hepatitis B viral infection is a serious risk factor for chronic hepatitis B (CHB), cirrhosis and hepatocellular carcinoma. Recently, several genome‐wide association studies (GWASs) have been conducted to identify important genetic variant associated with the risk of CHB. In our previous GWAS, TCF19 was identified as one of the susceptibility genes for CHB risk ( P =4.2×10 −9 at rs1419881 ). In order to discover possible additional causal variants around TCF19, we performed an association study by genotyping single nucleotide polymorphisms (SNPs) in OCT4, a nearby gene to TCF19 . Methods: Nineteen OCT4 genetic variants were selected and genotyped in 3902 subjects (1046 CHB patients and 2856 population controls). Results: Logistic regression analysis revealed that OCT4 rs1265163 showed the most significant association signal for the risk of CHB (OR=1.46, P =4.78×10 −12 ). Linkage disequilibrium and conditional analysis confirmed rs1265163 in OCT4 as a novel genetic marker for CHB susceptibility. The genetic risk scores (GRSs) were calculated to visualize the combined genetic effects of all known CHB‐associated loci, including OCT4 rs1265163, which had been identified in this study. Individuals with higher cumulative GRSs showed significantly increased ORs. The luciferase activity of rs885952, a tagging SNP of rs1265163, showed that OCT4 promoter activity was significantly different between the wild‐type and SNP mutant form ( P <.05). Conclusions: This follow‐up study to our previous GWAS identified a possible causal genetic variant associated with the risk of CHB, and findings from this study may prove useful in the understanding of genetic susceptibility to CHB.